FAVOURABLE CULTURE CONDITIONS FOR MYCELIAL GROWTH OF HYDNUM REPANDUM, A MEDICINAL MUSHROOM - Peksen, Aysun; Kibar, Beyhan; Yakupoglu, Gokcen (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
In this study, factors such as pH, temperature, carbon and nitrogen sources that affect mycelial growth of Hydnum repandum, amedicinal mushroom, were investigated. Different inoculum media for vegetative inoculum production were also examined. The best suitable pHfor mycelial growth was found to be 5.5. Among constant temperatures, the best mycelial growth was obtained at 20 and 25°C. The mycelialgrowth drastically decreased at 15°C, and no mycelia were obtained at 30°C. Glucose and mannitol were found to be the most suitable carbonsources. Ca(NO 3 ) 2 as a nitrogen source gave the best results for mycelial growth. The poorest mycelial growth was noted in sucrose and xylose ascarbon sources and in NH 4 NO 3 and (NH 4 ) 2 HPO 4 as nitrogen sources. Peat and peat: vermiculite mixtures (1:4, 1:6, 1:8 and 1:10, v:v) were thebest media to use in producing the vegetative inoculum of H. repandum